Ecological Conscience and Peace in the Social Doctrine of the Church - Caporali, Fabio (Studia Ecologiae et Bioethicae, 2024)
In a time when wars emerge again with their devastating effects, both material and spiritual, there is an indispensable need to build a peace-making culture based on ecological conscience. After highlightening the transdisciplinary process of emergence and development of an ecological conscience through the prophetic insights of scientists, philosophers and theologians, the recent contributions of the Social Doctrine of the Church are summarized with their content of innovation and faith in both a peaceful human society and a sustainable planetary community. Suggestions for ecolinguistic developments and improvements in favor of ecological conscience and peace-bulding attitudes are both recognised and advanced as meaningful tools for positive “framing” in a communication society. Innovative conceptual terms, like natural capital, biosphere, noosphere, anthropocene, ecosystem services, sustainability, integral ecology, ecological spirituality and ecological conversion are recognised as typical eco-linguistic emergences arisen within a context of holistic framing of reality. They constitute the eco-linguistic cascade that has innovated the recent development of the social doctrine of the Church such as that expressed in the Encyclical Letters and in The World Days of Peace Messages for building a culture of peace based on ecological conscience. The Church’s contribution to the advancement of ecological conscience has been exemplary for providing human beings with the necessary spiritual energy to become “peace operators.”